VTUBER PERSONAS IN DIGITAL WAYANG: A REVIEW OF INNOVATIVE CULTURAL PROMOTION FOR INDONESIAN HERITAGE (Jurnal Pilar Nusa Mandiri, 2024)
This study investigates the integration of VTuber into Wayang Digital as a strategic initiative to promote Indonesian cultural heritage. By leveraging advanced technologies such as real-time motion capture and artificial intelligence (AI), the project aims to enhance the animation quality and interaction of VTuber, creating a more immersive and engaging experience for audiences. The research focuses on three key aspects: VTuber integration's effectiveness in attracting international audiences, optimizing real-time motion capture for high-quality animation, and applying AI algorithms to create adaptive, responsive interactions between VTubers and their viewers. Through these innovations, the study aims to enrich the narrative and visual appeal of Wayang Digital, making it more accessible and appealing to a diverse global audience. The findings show that integrating advanced technologies enhances Wayang Digital's storytelling, aesthetics, and effectiveness as a powerful tool for cultural promotion. AI-enabled adaptive interactions create a personalized viewer experience, deepening audience connections with the traditional art form. High-quality animation preserves and effectively communicates Wayang's cultural nuances to audiences, enhancing its impact and cultural promotion. This study underscores the importance of continuous technological innovation and strategic implementation in the preservation and globalization of Indonesian heritage through digital media, suggesting that the future of cultural preservation lies in the seamless integration of tradition with cutting-edge technology.